Effect of Sea Water and Natural Ageing on Residual Strength of Epoxy Laminates, Reinforced with Glass and Carbon Woven Fabrics - Andrzej Komorek; Paweł Przybyłek; Wojciech Kucharczyk (Advances in Materials Science and Engineering)
This paper reports the results of the effect of sea water, natural ageing, and cross-impact loading on flexural strength and residual flexural strength of epoxy laminates with glass woven fabrics and hybrid reinforcement with glass and carbon woven fabrics. The tests were conducted on samples with different fibre reinforcement both before and after low energy cross-impact loading. Carbon fabrics decreased residual strength of the composites.